Pendampingan dan Edukasi Petani Padi dalam Penerapan Pertanian Berkelanjutan Organik di Desa Sukorame - Sunarto; Dewi, Rifani Rusiana; Pamujiati, Agustia Dwi; Hadiyanti, Nugraheni; Tafakresnanto, Chendy (Kadiri University, 2024)
Pesticides are one of the components of agri input needed to protect plants from plant pests. However, massive use of pesticides can cause various negative impacts on plants, the environment, and human health. Excessive use of pesticides in rice cultivation is still a problem that is often found in Sukorame Village, Trenggalek. Seeing this condition, there needs to be more intensive education efforts for farmers. Seeing this problem, community service activities were carried out by the Faculty of Agriculture team at Kadiri University. Community service activities were carried out with the aim of providing education to farmers regarding more environmentally friendly and sustainable pest management. This program is also expected to reduce dependence on chemical pesticides and introduce Integrated Pest Management (IPM) techniques that can help farmers increase productivity without damaging the environment. Community service activities were carried out using the Participatory Aural Appraisal (PRA) approach. This method emphasizes community participation and involvement starting from the preparation, education, training and mentoring stages. Overall, the main objectives of the program to increase farmer awareness of the dangers of pesticides and introduce the IPM method have been achieved. The community began to understand the importance of environmentally friendly pest management. After the program was implemented, farmers began to provide follow-up. It is seen that some farmers have started to adopt the IPM method as a sustainable agricultural system. Pestisida merupakan salah satu komponen agri input yang dibutuhkan untuk melindungi tanaman dari organisme pengganggu tanaman. Namun, penggunaan pestisida secara masif dapat menimbulkan berbagai dampak negatif, baik bagi tanaman, lingkungan, maupun kesehatan manusia. Penggunaan pestisida berlebihan dalam budidaya padi masih menjadi masalah yang sering dijumpai di Desa Sukorame, Trenggalek. Melihat kondisi ini, perlu adanya upaya edukasi yang lebih intensif kepada para petani. Melihat permasalahan tersebut, maka dilakukan kegiatan pengabdian masyarakat oleh tim Fakultas Pertanian Universitas Kadiri. Kegiatan pengabdian masyarakat dilakukan dengan tujuan memberikan edukasi kepada petani terkait pengelolaan hama yang lebih ramah lingkungan dan berkelanjutan. Program ini juga diharapkan dapat mengurangi ketergantungan pada pestisida kimia dan memperkenalkan teknik Integrated Pest Management (IPM) yang dapat membantu petani meningkatkan produktivitas tanpa merusak lingkungan. Kegiatan pengabdian masyarakat dilakukan dengan pendekatan Participatory Aural Appraisal (PRA). Metode ini menekankan partisipasi dan keterlibatan masyarakat mulai dari tahap persiapan, edukasi, pelatihan dan pendampingan. Secara keseluruhan, tujuan utama program untuk meningkatkan kesadaran petani tentang bahaya pestisida dan memperkenalkan metode IPM telah tercapai. Masyarakat mulai memahami pentingnya pengelolaan hama ramah lingkungan. Setelah pelaksanaan program, petani mulai memberikan tindak lanjut. Hal ini terlihat bahwa beberapa petani mulai mengadopsi metode IPM sebagai salah satu sistem pertanian berkelanjutan.